Evaluation of The Impacted Maxillary Canines Effect on The Adjacent Teeth Roots and Alveolar Bone Dimensions Using Cone Beam Computed Tomography (Journal of Hama University, 2020)
The purpose of this study was to evaluate the effect of the impacted maxillary canines on the adjacent teeth roots and aleveolar bone dimensions by using Cone Beam Computed Tomography.32 patients with the mean age of 20,3 years and unilateral  impacted maxillary  canines were involved.CBCT images were taken to evaluate the study variables by using EZ 3D plus software.The evaluation of the adjacent central and lateral incisors roots resorption was made considering axial sections obtained from the cervical region to the apical region with thickness of 1 mm, perpendicular to the long axis of this teeth.Two reference lines were used for measurement standarization (aleveolar height, buccopalatal width and Arch perimeter) which were measured on both the impacted and non-impacted sides.Data were analyzed by using Independent Samples T test and Mann-Whitney U test at (P=0,05).  According to the result of this study: The highest percentage of the resorption was in the middle third of the adjacent teeth roots of the impacted canine (46,9%), Percentages of the resorption  degrees were (35,9% slight degree, 4,7% moderat degree, 9,4% serve degree).This study shows statistically significant differences in aleveolar bone height  between the impacted and non-impacted sides (P< 0.05) The aleveolar bone height was significantly reduced on the impacted when compared to non-impacted side.